In-field critical current performance of 4.0 μm thick film REBCO conductor with Hf addition at 4.2 K and fields up to 31.2 T. (12th June 2020) - Majkic, Goran; Pratap, Rudra; Paidpilli, Mahesh; Galstyan, Eduard; Kochat, Mehdi; Goel, Chirag; Kar, Soumen; Jaroszynski, Jan; Abraimov, Dmytro; Selvamanickam, Venkat
Abstract: We present results on the in-field critical current ( Ic ) performance of 4.0 μ m thick REBCO film with 15% Hf addition with fields up to 31.2 T and field orientations in the B║ab plane and B║c axis. Unlike the behavior at B║c, the critical current at B║ab is only very weakly dependent on field, decreasing from self-field to 31.2 T by only 22%, i.e. from the self-field value of ∼7700 A/4 mm width to ∼6300 and 5812 A/4 mm width at 14 and 30 T, respectively. These values are remarkably 3 and 5.7x higher than the corresponding critical currents at B║c. The in-field behavior of the present 15% Hf sample at field orientation B║c axis is nearly identical to the previously reported record values found in 4.3 and 4.6 μ m thick 15% Zr samples in terms of critical current density. In contrast to the pinning force behavior in the B║c orientation, which saturates to a constant value of 1.7 TN m −3 above ∼5–6 T, the pinning force in the B║ab orientation increases near-linearly, reaching a remarkable value of over 11.5 TN m −3 at 31.2 T. These results demonstrate the potential of thick REBCO conductors at 4.2 K for high field and energy density applications, in particular where the magnetic field is contained near the ab-plane.